Sodium hyaluronate composite filler for injection as well as preparation method and application of sodium hyaluronate composite filler
By introducing methoxy polyethylene glycol-polyl lactic acid nanoparticles into the polylactic acid microsphere filler, the sodium hyaluronate composite filler is solved, and the redissolution difficulty of polylactic acid microsphere filler in the prior art is solved. The problems of poor dispersion and risk of inflammatory reactions have achieved high biocompatibility, good injection and rapid onset filling effects.
Patent Information
- Application Number
- CN202411552878.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing polylactic acid microsphere fillers have difficulty redissolving, poor dispersion, easy aggregation and deposition, and the risk of inflammatory reactions when intradermal injection, and the onset time is relatively slow.
Using a sodium hyaluronate composite filler containing methoxy polyethylene glycol-polylevolactate nanoparticles, the nanoparticle structure is formed by combining methoxy polyethylene glycol-polylevolactate polymer with sodium hyaluronate. , improve biocompatibility and degradability, and improve injection and filling effects.
It achieves high biocompatibility, good dispersion and injection properties, reduces the risk of subcutaneous nodules and inflammatory reactions, and can stimulate collagen regeneration faster and better, significantly improves the filling effect and onset time.
Smart Images

Figure CN119405891A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and in particular relates to a sodium hyaluronate composite filler for injection, and a preparation method and application thereof. Background Art
[0002] In recent years, injectable fillers for cosmetic and medical purposes have developed rapidly. Injectable fillers can achieve the cosmetic effect of supporting and filling at the injection site and have received widespread attention. Sodium hyaluronate, as an acidic mucopolysaccharide widely present in human connective tissue, has the function of stabilizing the extracellular matrix. Because of its strong water absorption capacity, it can maintain the elasticity of the skin and retain moisture, and is widely used in injection micro-plastic surgery. However, while it has good biocompatibility and degradability, it will also be rapidly degraded in the body. This problem is often solved by cross-linking with diepoxides. However, with the increase in the degree of cross-linking, the granularity of hyaluronic acid and the resulting inflammatory response are gradually enhanced, and there is even a risk of granuloma. Therefore, simply increasing the maintenance time of hyaluronic acid by cross-linking is risky. To avoid the risk of inflammation and prolong the effect, one way is to add other ingredients to the hyaluronic acid gel. Among them, compared with materials from animal sources, artificial chemically synthesized polymer materials have reduced the risk of infectious diseases and are safe to use, so they are increasingly favored by the majority of beauty lovers. However, artificially synthesized polymer materials should have good biocompatibility before they can be used in mixed gels. However, not all materials are suitable as additives to hyaluronic acid gel. In order to be evenly mixed in the hyaluronic acid gel and not easily aggregate after being injected into the human body, the material must be both lipophilic and hydrophilic, that is, amphiphilic.
[0003] However, traditional polylactic acid microsphere injection products are not easy to redissolve due to poor hydrophilicity, and the polylactic acid microspheres after redissolution have poor dispersibility and are easy to aggregate and deposit, which causes problems such as easy needle blockage during intradermal injection, easy appearance of subcutaneous nodules after injection, and thicker needles used during injection, which leads to increased pain in patients. Sometimes sodium carboxymethyl cellulose (CMC) is used as a suspending agent to improve the above-mentioned disadvantages, such as the listed products Avilan and Sculptra. However, CMC is not an endogenous substance in the human body and has poor biocompatibility. In addition, polylactic acid microsphere products using CMC as a suspending agent generally require a long period of hydration before they can be used for intradermal injection, which brings inconvenience to the application.
[0004] In 2021, a facial filler named Rubai Angel was launched. It is a cross-linked sodium hyaluronate gel containing L-lactic acid-ethylene glycol copolymer microspheres. The particle size of the L-lactic acid-ethylene glycol copolymer microspheres is 20-45 μm. It is easy to inject and can be injected immediately without re-dissolving. The compound cross-linked hyaluronic acid has an immediate filling effect, and the poly-L-lactic acid subsequently stimulates collagen regeneration. However, all polylactic acid microsphere products, including Rubai Angel, have a relatively slow onset of effect. The real effect is not seen until 2 weeks after injection, and it reaches its peak after 3 to 6 months. Summary of the invention
[0005] The purpose of the present invention is to provide an injectable sodium hyaluronate composite filler and a preparation method and application thereof, specifically an injectable sodium hyaluronate composite filler containing methoxy polyethylene glycol-poly-L-lactic acid nanoparticles and a preparation method and application thereof, so as to solve the deficiencies of the prior art.
[0006] In a first aspect, the present invention provides a sodium hyaluronate composite filler for injection, comprising methoxy polyethylene glycol-poly-L-lactic acid nanoparticles, sodium hyaluronate and a dispersion medium; the concentration of the methoxy polyethylene glycol-poly-L-lactic acid nanoparticles in the dispersion medium is 5 mg / mL to 300 mg / mL, for example, 5 mg / mL to 50 mg / mL, 50 mg / mL to 100 mg / mL, 100 mg / mL to 150 mg / mL, 150 mg / mL to 200 mg / mL or 200 mg / mL to 300 mg / mL.
[0007] The concentration of sodium hyaluronate in the dispersion medium is 5 mg / mL to 30 mg / mL, for example, 5 mg / mL to 10 mg / mL, 10 mg / mL to 15 mg / mL, 15 mg / mL to 20 mg / mL or 20 mg / mL to 30 mg / mL.
[0008] The dispersion medium is water, physiological saline, glucose solution or phosphate buffer; the average particle size of the methoxy polyethylene glycol-poly L-lactic acid nanoparticles is 10-500 nm, for example, 10-50 nm, 50-100 nm, 100-200 nm, 200-300 nm, 300-400 nm or 400-500 nm. The polydispersity index (PDI) of the methoxy polyethylene glycol-poly L-lactic acid nanoparticles is 0.05-0.4, for example, 0.05-0.1, 0.1-0.2, 0.2-0.3 or 0.3-0.4.
[0009] The sodium hyaluronate composite filler is in a gel state and does not need to be re-dissolved during use and can be directly injected for use.
[0010] In the sodium hyaluronate composite filler containing methoxy polyethylene glycol-poly-L-lactic acid nanoparticles, the molecular weight of sodium hyaluronate is 2×105 ~2.5×10 6 Dalton. For example, 6×10 5 ~2.5×10 6 Dalton.
[0011] In the sodium hyaluronate composite filler containing methoxy polyethylene glycol-poly-L-lactic acid nanoparticles, the molecular weight of the methoxy polyethylene glycol block in the methoxy polyethylene glycol-poly-L-lactic acid polymer is 500-10000 Daltons, preferably 1000-5000 Daltons, for example, 1000-1500 Daltons, 1500-3000 Daltons or 3000-5000 Daltons; the molecular weight of the poly-L-lactic acid block in the methoxy polyethylene glycol-poly-L-lactic acid polymer is 500-20000 Daltons, preferably 1000-10000 Daltons, for example, 1000-1500 Daltons, 1500-3000 Daltons, 3000-5000 Daltons or 5000-10000 Daltons.
[0012] The second aspect of the present invention provides a preparation method of the sodium hyaluronate composite filler for injection, the specific steps are: 1) mixing an organic solvent with a methoxy polyethylene glycol-poly-L-lactic acid polymer to obtain an oil phase, wherein the mass fraction of the methoxy polyethylene glycol-poly-L-lactic acid polymer in the oil phase is 0 to 20%, excluding 0, for example 1%, 3%, 5%, 10%, 12%, 15%, 18% or 20%.
[0013] 2) After removing the organic solvent, add distilled water for hydration (the amount of distilled water added is determined according to the amount of methoxy polyethylene glycol-poly-L-lactic acid polymer, generally 5 to 20 times the mass of the polymer), let it stand for 15 to 60 minutes (e.g. 15 to 30 minutes, 30 to 60 minutes) to obtain a methoxy polyethylene glycol-poly-L-lactic acid nanoparticle solution; specifically, the oil phase is rotary evaporated under vacuum conditions for 10 to 120 minutes to remove the organic solvent; then add an appropriate amount of distilled water for hydration for 10 to 60 minutes to obtain a nanoparticle aqueous solution with a concentration of 1 mg / mL to 100 mg / mL of methoxy polyethylene glycol-poly-L-lactic acid nanoparticles, which can be 1 mg / mL to 5 mg / mL, 5 mg / mL to 20 mg / mL, 20 mg / mL to 50 mg / mL or 50 mg / mL to 100 mg / mL. 。
[0014] 3) Freeze drying to obtain methoxy polyethylene glycol-poly-L-lactic acid nanoparticle freeze-dried powder. There are no special requirements for freeze drying conditions, and basically all freeze drying equipment can be used. The freeze drying temperature is -50°C to -40°C, and the time is 12 to 72 hours. The specific time can be set according to needs.
[0015] 4) providing a hyaluronic acid solution that is completely swollen in a dispersion medium;
[0016] 5) re-dissolving the methoxy polyethylene glycol-poly (L-lactic acid) nanoparticle freeze-dried powder prepared in step 3) with a dispersion medium to obtain a nanoparticle solution;
[0017] 6) adding the nanoparticle solution of step 5) to the hyaluronic acid solution of step 4) to obtain a sodium hyaluronate composite filler of methoxy polyethylene glycol-poly-L-lactic acid nanoparticles.
[0018] The third aspect of the present invention is the use of the sodium hyaluronate composite filler described above or the sodium hyaluronate composite filler prepared by any of the preparation methods described above in tissue repair materials and / or filling biomaterials.
[0019] The beneficial effects of the present invention are at least:
[0020] 1. The composite filler of the present invention has high biocompatibility. The polymer nanoparticles are more easily dispersed evenly due to their hydrophilic surface, which is beneficial to reducing the appearance of subcutaneous nodules and does not block blood vessels. At the same time, due to the loose structure of the nanoparticles, they have good biodegradability and can stimulate collagen regeneration faster and better.
[0021] 2. The sodium hyaluronate composite filler product containing methoxy polyethylene glycol-poly-L-lactic acid nanoparticles for injection provided by the present invention is uniform and fine, has good needle permeability, is easy to inject, does not require re-dissolution, and is simple to operate;
[0022] 3. It has no irritation to the skin, has a long local retention time, good plasticity, and few side effects. It can stimulate collagen regeneration faster and better, thus significantly eliminating wrinkles;
[0023] 4. The preparation process conditions of the present invention are easy to control, the operation steps are few, and the product quality is stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the particle size diagram of methoxy polyethylene glycol-poly (L-lactic acid) nanoparticles prepared in Example 1.
[0025] Figure 2 State diagrams of composite fillers prepared from sodium hyaluronate with different molecular weights prepared in Examples 1, 2 and 3, wherein a is a top view, b is a front view, 1) is the composite filler prepared in Example 1, 2) is the composite filler prepared in Example 2, and 3) is the composite filler prepared in Example 3.
[0026] Figure 3 State diagrams of composite fillers containing different concentrations of methoxypolyethylene glycol-poly-L-lactic acid nanoparticles prepared in Examples 4 and 5, wherein a is a top view, b is a front view, 1) is the composite filler prepared in Example 4, and 2) is the composite filler prepared in Example 5.
[0027] Figure 4 State diagrams of the composite fillers containing different concentrations of methoxypolyethylene glycol-poly-L-lactic acid nanoparticles prepared in Examples 6 to 10, 1) the composite filler prepared in Example 6, 2) the composite filler prepared in Example 7, 3) the composite filler prepared in Example 8, 4) the composite filler prepared in Example 9, and 5) the composite filler prepared in Example 10.
[0028] Figure 5 The test results of collagen volume ratio in test example 4 are shown in Figure 1. Group 1 is the normal saline group, and Group 2 is the commercially available moist white angel TM Facial fillers, group 3 is 100 mg / mL nanoparticles / high molecular weight sodium hyaluronate, and group 4 is 200 mg / mL nanoparticles / high molecular weight sodium hyaluronate.
[0029] Figure 6 The graph is the test result of the percentage of new type III collagen fibers in test example 4. Group 1 is the normal saline group, and Group 2 is the commercially available moist white angel TM Facial fillers, group 3 is 100 mg / mL nanoparticles / high molecular weight sodium hyaluronate, and group 4 is 200 mg / mL nanoparticles / high molecular weight sodium hyaluronate. DETAILED DESCRIPTION
[0030] The following examples are intended to illustrate the present invention rather than to further limit the present invention. The present invention is further described in detail below with reference to the examples, but the present invention is not limited to these examples and the preparation methods used. Moreover, those skilled in the art can carry out equivalent replacement, combination, improvement or modification to the present invention based on the description of the present invention, but these will all be included in the scope of the present invention.
[0031] Example 1
[0032] 1. Preparation of methoxy polyethylene glycol-poly (L-lactic acid) nanoparticles.
[0033] 1) In a round bottom flask, add the polymer methoxy polyethylene glycol 2000 -Poly-L-lactic acid 1300 (mPEG 2000 -b-PLLA 1300 ) 100 mg was dissolved in 10 mL of acetonitrile to obtain an oil phase;
[0034] 2) Use a rotary evaporator to evaporate the acetonitrile in a 60°C water bath to allow the polymer to form a uniform film on the wall of the device, then hydrate with 10 mL of deionized water and let stand for 30 minutes to fully self-assemble to form a nanoparticle solution, such as Figure 1As shown, the particle size of methoxy polyethylene glycol-poly-L-lactic acid nanoparticles measured by dynamic light scattering method is 98.53 nm, and the polydispersity index (PDI) is 0.228, indicating that the obtained nanoparticles have a small particle size and a uniform particle size distribution.
[0035] 3) freeze-drying the obtained nanoparticle solution for 48 hours to obtain methoxy polyethylene glycol-poly-L-lactic acid nanoparticle freeze-dried powder.
[0036] 2. Prepare sodium hyaluronate composite filler containing methoxy polyethylene glycol-poly (L-lactic acid) nanoparticles.
[0037] 4) Weigh 213 mg of a molecular weight of 2.3×10 6 Dalton's hyaluronic acid (Shandong Zhongshan Biotechnology Co., Ltd.) was placed in a 10 mL volumetric flask, and distilled water was added. After 48 hours, it was completely swollen (the amount of distilled water added was to ensure that the hyaluronic acid was completely swollen), and the volume was fixed to obtain hyaluronic acid solution A. The density of the solution was measured to be 0.99 g / mL.
[0038] 5) Redissolve 1 g of methoxypolyethylene glycol-poly-L-lactic acid nanoparticle freeze-dried powder with 1 mL of distilled water to obtain a nanoparticle solution with a concentration of 1 g / mL.
[0039] 6) Weigh 7.9 g of hyaluronic acid solution A (actually containing 170 mg of hyaluronic acid) into a 10 mL volumetric flask, add 1 mL of the above nanoparticle solution, dilute to 10 mL with distilled water and mix well to obtain methoxy polyethylene glycol-poly-L-lactic acid nanoparticles and sodium hyaluronate composite filler A, wherein the concentration of methoxy polyethylene glycol-poly-L-lactic acid nanoparticles is 100 mg / mL, and the concentration of sodium hyaluronate is 17 mg / mL.
[0040] Example 2
[0041] The difference from Example 1 is that in step 4), the molecular weight of hyaluronic acid is 1.15×10 6 Dalton, hyaluronic acid solution B was obtained, and the density of the solution was measured to be 1.0 g / mL. In step 6), 7.98 g of hyaluronic acid solution A (actually containing 170 mg of hyaluronic acid) was weighed into a 10 mL volumetric flask. Finally, methoxy polyethylene glycol-poly-L-lactic acid nanoparticles sodium hyaluronate composite filler B was obtained.
[0042] Example 3
[0043] The difference from Example 1 is that in step 4), the molecular weight of hyaluronic acid is 6 to 7×10 5Dalton, a hyaluronic acid solution C was obtained, and the density of the solution was measured to be 1.0 g / mL. In step 6), 7.98 g of hyaluronic acid solution A (actually containing 170 mg of hyaluronic acid) was weighed into a 10 mL volumetric flask. Finally, a sodium hyaluronate composite filler C of methoxy polyethylene glycol-poly-L-lactic acid nanoparticles was obtained.
[0044] The state diagram of the composite filler prepared by sodium hyaluronate with different molecular weights is shown in Figure 2 ,Depend on Figure 2 It can be seen that the composite fillers prepared with sodium hyaluronate of different molecular weights are all in the form of milky white viscous gel. When injected in the shallow layer, they can avoid the light transmittance and Tyndall phenomenon that may occur in transparent hyaluronic acid, and the filling effect is more real and natural.
[0045] Example 4
[0046] The difference from Example 1 is that
[0047] In step 5), 2 g of methoxypolyethylene glycol-poly-L-lactic acid nanoparticle freeze-dried powder is reconstituted with 1 mL of distilled water to obtain a nanoparticle solution with a concentration of 2 g / mL.
[0048] In step 6), 7.9 g of hyaluronic acid solution A (actually containing 170 mg of hyaluronic acid) was weighed into a 10 mL volumetric flask, 0.5 mL of the nanoparticle solution in step 5) was added, and the volume was adjusted to 10 mL with distilled water and mixed evenly to obtain a sodium hyaluronate composite filler D containing 100 mg / mL methoxypolyethylene glycol-poly-L-lactic acid nanoparticles, and the sodium hyaluronate concentration was 17 mg / mL.
[0049] Example 5
[0050] The difference from Example 1 is that
[0051] In step 5), 2 g of methoxypolyethylene glycol-poly-L-lactic acid nanoparticle freeze-dried powder is reconstituted with 1 mL of distilled water to obtain a nanoparticle solution with a concentration of 2 g / mL.
[0052] In step 6), 7.9 g of hyaluronic acid solution A (actually containing 170 mg of hyaluronic acid) was weighed into a 10 mL volumetric flask, 1 mL of the above-mentioned nanoparticle solution was added, and the volume was adjusted to 10 mL with distilled water and mixed evenly to obtain a sodium hyaluronate composite filler D containing 200 mg / mL methoxypolyethylene glycol-poly-L-lactic acid nanoparticles, and the sodium hyaluronate concentration was 17 mg / mL.
[0053] The state diagram of the composite filler containing different concentrations of methoxy polyethylene glycol-poly (L-lactic acid) nanoparticles is shown in Figure 2. Figure 3 ,Depend on Figure 3It can be seen that the composite fillers containing different concentrations of methoxypolyethylene glycol-poly-L-lactic acid nanoparticles are all milky white viscous gel-like. When injected in the shallow layer, they can avoid the light transmittance and Tyndall phenomenon that may occur in transparent hyaluronic acid, and the filling effect is more realistic and natural.
[0054] Embodiments 6 to 10
[0055] This group of examples prepares composite fillers containing different concentrations of methoxy polyethylene glycol-poly-L-lactic acid nanoparticles. The difference from Example 1 is that:
[0056] Step 4) Weigh 213 mg of hyaluronic acid (molecular weight 6×10 5 Dalton) in a 10 mL volumetric flask, add an appropriate amount of distilled water, wait for 48 hours until it is completely swollen, and then make up to volume to obtain a hyaluronic acid solution.
[0057] Step 5) reconstitute 1 g of methoxypolyethylene glycol-poly-L-lactic acid nanoparticle freeze-dried powder with 1 mL of distilled water to obtain a nanoparticle solution with a concentration of 1 g / mL.
[0058] Step 6) Weigh 2.32 g (actually containing 50 mg of hyaluronic acid) of the above five portions of hyaluronic acid solution into five different 10 mL volumetric flasks, add 0.05 mL, 0.1 mL, 0.2 mL, 0.3 mL, and 0.5 mL of the above nanoparticle solution, dilute to 10 mL with distilled water, and mix evenly to obtain sodium hyaluronate composite fillers containing 5 mg / mL, 10 mg / mL, 20 mg / mL, 30 mg / mL, and 50 mg / mL methoxypolyethylene glycol-poly-L-lactic acid nanoparticles, respectively.
[0059] Test Example 1
[0060] With different molecular weight (2.3×10 6 Dalton, 1.15×10 6 Dalton, molecular weight is 6~7×10 5 Dalton's sodium hyaluronate solution (concentration of 17 mg / mL) was used as a control, and the needle permeability of a total of 7 composite fillers prepared in Examples 4 to 10 was investigated. The results are shown in Table 1.
[0061] Table 1
[0062]
[0063] It can be seen that the needle permeability of the 7 tested products is good.
[0064] Test Example 2
[0065] The states of the various composite fillers prepared in Examples 6 to 10 were examined and the results are shown in Table 2.
[0066] Table 2
[0067]
[0068] It can be seen that the fillers of various prescriptions are milky white. When the nanoparticle content is low, the transparency of the composite filler is better. As the concentration of nanoparticles increases, the transparency weakens to opaque. Since the milky white composite gel can effectively reduce the light transmission problem of the shaping part, the effect is more real and natural.
[0069] Test Example 3
[0070] The composite filler samples containing methoxy polyethylene glycol-poly-L-lactic acid nanoparticles prepared in Examples 4 to 10 were used to verify the skin irritation and displacement of the implanted part as a skin filler. The specific experimental method is as follows:
[0071] Samples to be tested: two samples of composite fillers containing different concentrations of methoxy polyethylene glycol-poly-L-lactic acid nanoparticles prepared in Examples 4 and 5, respectively marked as 100 mg / mL nanoparticles / high molecular weight sodium hyaluronate and 200 mg / mL nanoparticles / high molecular weight sodium hyaluronate; five samples of composite fillers containing different concentrations of methoxy polyethylene glycol-poly-L-lactic acid nanoparticles prepared in Examples 6 to 10, respectively marked as 5 mg / mL nanoparticles / low molecular weight sodium hyaluronate, 10 mg / mL nanoparticles / low molecular weight sodium hyaluronate, 20 mg / mL nanoparticles / low molecular weight sodium hyaluronate, 30 mg / mL nanoparticles / low molecular weight sodium hyaluronate, 50 mg / mL nanoparticles / low molecular weight sodium hyaluronate; commercially available moist white angel TM Facial fillers served as the positive control group, and normal saline served as the blank control group.
[0072] Experimental animals: Purebred New Zealand white rabbits aged 4 to 6 months, weighing 210 to 215 g, were divided into 3 groups (corresponding to three time points), with 9 rabbits in each group;
[0073] Injection: On the day of implantation, the rabbit's back was shaved, iodine and ethanol were routinely disinfected, and 6 points (0.5 mL / point) were injected subcutaneously at 3 cm intervals on both sides of the spine. The left and right symmetrical injection points were a group of samples to be tested, and then the injection points were marked with Coomassie Brilliant Blue. The injection points were supplemented with color every two weeks to prevent fading due to metabolism.
[0074] Detection method:
[0075] The skin appearance of the implanted area was observed every day for one month after implantation to see if there was redness, swelling or bulge; the injected local tissue was touched to see if there was nodule or granulation tissue proliferation. The animals were not killed. The experimental results are shown in Table 2.
[0076] The experimental animals were killed at three time points after implantation (1 month, 3 months, and 6 months), with 9 animals killed at each time point. The subcutaneous tissue including the implanted material was excised and placed in a 10% formaldehyde solution. After fixation for 48 hours, the sections were routinely dehydrated, transparent, waxed, embedded, and routinely sectioned. The section thickness was 3 μm. After the paraffin sections were dewaxed to water, the sections were immersed in hematoxylin staining solution for 5 minutes, washed and separated, and then immersed in eosin staining solution for 2 minutes. After dehydration and sealing, the sections were examined under a microscope. The results are shown in Table 3.
[0077] Table 3
[0078]
[0079] / : Indicates not applicable here.
[0080] It can be seen from Table 3 that, compared with the marketed products, the seven tested samples showed no adverse skin appearance reactions after being implanted subcutaneously in the back of rabbits, and there was no obvious inflammatory reaction or risk of displacement, indicating that the tested samples have good biocompatibility, high safety, and can achieve precise positioning and filling of the injection site.
[0081] Test Example 4
[0082] The composite filler samples containing methoxy polyethylene glycol-poly-L-lactic acid nanoparticles prepared in Examples 4 and 5 were used to verify their ability to stimulate collagen regeneration as skin fillers. The specific experimental method is as follows:
[0083] Samples to be tested: two samples of composite fillers containing different concentrations of methoxypolyethylene glycol-poly-L-lactic acid nanoparticles prepared in Examples 4 and 5, respectively labeled as 200 mg / mL nanoparticles / high molecular weight sodium hyaluronate (Group 4), 100 mg / mL nanoparticles / high molecular weight sodium hyaluronate (Group 3), commercially available moist angel TM The facial filler served as the positive control group (Group 2), and normal saline served as the blank control group (Group 1).
[0084] Experimental animals: Purebred New Zealand white rabbits aged 4 to 6 months, weighing 210 to 215 g, were divided into 3 groups (corresponding to three time points), with 3 rabbits in each group;
[0085] Injection: On the day of implantation, the rabbits were shaved on the back, routinely disinfected with iodine and ethanol, and injected at 8 points (0.5 mL / point) at 2 cm intervals on both sides of the spine. The left and right symmetrical injection points were a group of samples to be tested. From top to bottom, they were group 4, group 3, group 2, and group 1. Then the injection points were marked with Coomassie brilliant blue. The injection points were supplemented with color every two weeks to prevent fading caused by metabolism.
[0086] Detection method:
[0087] The experimental animals were killed at three time points (1 month, 3 months, and 6 months) after implantation, with three animals killed at each time point. The subcutaneous tissue including the implanted materials was excised and placed in a 10% formaldehyde solution. After fixation for 48 hours, the tissue was routinely dehydrated, transparent, wax-impregnated, embedded, and routinely sectioned. The thickness of the sections was 3 μm, and Masson staining and Sirius red staining were performed.
[0088] Masson staining: After paraffin sections were dewaxed to water, the sections were immersed in potassium dichromate overnight, then stained with iron hematoxylin for 1 min, stained with ponceau acid fuchsin for 6 min, stained with phosphomolybdic acid for 1 min, and stained with aniline blue for 30 s. After dehydration and sealing, they were examined under a microscope. Three sections filled with cell tissue were randomly selected for each section under a 200x microscope, and the mean percentage of the collagen-positive area of the three sections to the total tissue area was calculated using Image-ProPlus 6.0 software. The results are shown in the attached Figure 5 .
[0089] Sirius red staining: Sirius red staining was performed after tissue fixation. An optical microscope equipped with a polarized light filter was used for microscopic examination. Three sections filled with cell tissue were randomly selected for each slice under a 200x microscope. The mean percentage of type III collagen in the three sections was calculated using Image-ProPlus 6.0 software. The results are shown in the attached Figure 6 .
[0090] from Figure 4 The results of collagen volume ratio show that after 1 month, 3 months and 6 months of injection, the collagen volume ratio of each test group was higher than that of the blank control group. The order of the groups at different time points from high to low is: 200mg / mL nanoparticles / high molecular weight sodium hyaluronate group>100mg / mL nanoparticles / high molecular weight sodium hyaluronate>Rubber Angel TM >Blank control group.
[0091] Depend on Figure 6 The results of the percentage of newly formed type III collagen fibers show that after 1 month, 3 months and 6 months of injection, the content of newly formed type III collagen fibers in each test group was higher than that in the blank control group. The ranking of the content of type III collagen fibers in each group at each time point from most to least is as follows: 200 mg / mL nanoparticles / high molecular weight sodium hyaluronate group>100 mg / mL nanoparticles / high molecular weight sodium hyaluronate>Rubber Angel TM >Blank control group.
[0092] Wet White Angel TM The content of L-lactic acid-ethylene glycol copolymer microspheres in the 100 mg / mL nanoparticles / high molecular weight sodium hyaluronate group was lower than that in the wet white angel. TMHowever, the collagen volume ratio and the percentage of newly formed type III collagen fibers in the 100 mg / mL nanoparticle / high molecular weight sodium hyaluronate group were higher than those in the wet angel at each time point. TM , indicating that the tested samples have better biodegradability and can promote collagen regeneration earlier and more beneficially, which has significant advantages compared with similar facial fillers.
Claims
1. A sodium hyaluronate composite filler for injection, characterized in that: It includes methoxy polyethylene glycol-poly (L-lactic acid) nanoparticles, sodium hyaluronate and a dispersion medium; The concentration of the methoxy polyethylene glycol-poly-L-lactic acid nanoparticles in the dispersion medium is 5 mg / mL to 300 mg / mL; The concentration of sodium hyaluronate in the dispersion medium is 5 mg / mL to 30 mg / mL; The average particle size of the methoxy polyethylene glycol-poly (L-lactic acid) nanoparticles is 10 nm to 500 nm.
2. The sodium hyaluronate composite filler according to claim 1, characterized in that: The molecular weight of sodium hyaluronate is 2×10 5 ~2.5×10 6 Dalton; and / or, the sodium hyaluronate composite filler is in a gel state; And / or, the polydispersity coefficient of the methoxy polyethylene glycol-poly-L-lactic acid nanoparticles is 0.05 to 0.
4.
3. The sodium hyaluronate composite filler according to claim 1, characterized in that: The raw materials for preparing the methoxy polyethylene glycol-poly-L-lactic acid nanoparticles include methoxy polyethylene glycol-poly-L-lactic acid polymer, wherein the molecular weight of the methoxy polyethylene glycol block in the methoxy polyethylene glycol-poly-L-lactic acid polymer is 500-10000 Daltons; the molecular weight of the poly-L-lactic acid block in the methoxy polyethylene glycol-poly-L-lactic acid polymer is 500-20000 Daltons.
4. The sodium hyaluronate composite filler according to claim 3, characterized in that: The concentration of the methoxy polyethylene glycol-poly-L-lactic acid nanoparticles in the dispersion medium is 100 mg / mL to 200 mg / mL; and / or, the concentration of the sodium hyaluronate in the dispersion medium is 10 to 20 mg / mL; And / or, the molecular weight of the sodium hyaluronate is 6×10 5 ~2.5×10 6 Dalton; And / or, the molecular weight of the methoxy polyethylene glycol block is 1000 to 5000 Daltons; the molecular weight of the poly-L-lactic acid block in the methoxy polyethylene glycol-poly-L-lactic acid is 1000 to 10000 Daltons.
5. The sodium hyaluronate composite filler according to any one of claims 1 to 4, characterized in that: The dispersion medium is one or a combination of at least two of water, physiological saline, glucose solution or phosphate buffer.
6. A method for preparing a sodium hyaluronate composite filler for injection, comprising the following steps: 1) mixing an organic solvent with a methoxy polyethylene glycol-poly-L-lactic acid polymer to obtain an oil phase; 2) After removing the organic solvent, adding distilled water for hydration, standing for 15 to 60 minutes, and obtaining a methoxy polyethylene glycol-poly-L-lactic acid nanoparticle solution; 3) freeze-drying to obtain methoxy polyethylene glycol-poly (L-lactic acid) nanoparticle freeze-dried powder; 4) providing a hyaluronic acid solution that is completely swollen in a dispersion medium; 5) re-dissolving the methoxy polyethylene glycol-poly (L-lactic acid) nanoparticle freeze-dried powder prepared in step 3) with a dispersion medium to obtain a nanoparticle solution; 6) adding the nanoparticle solution of step 5) to the hyaluronic acid solution of step 4) to obtain a sodium hyaluronate composite filler of methoxy polyethylene glycol-poly-L-lactic acid nanoparticles.
7. The preparation method according to claim 6, characterized in that: In step 1), the molecular weight of the methoxy polyethylene glycol block in the methoxy polyethylene glycol-poly-L-lactic acid polymer is 500 to 10,000 Daltons; the molecular weight of the poly-L-lactic acid block in the methoxy polyethylene glycol-poly-L-lactic acid polymer is 500 to 20,000 Daltons; And / or, the mass fraction of methoxy polyethylene glycol-poly-L-lactic acid in the oil phase in step 1) is 0 to 20%, excluding 0; And / or, in step 3), the freeze-drying temperature is -50°C to -40°C, and the time is 12 to 72 hours; And / or, in step 2), the concentration of the methoxy polyethylene glycol-poly-L-lactic acid nanoparticle solution is 1 mg / mL to 100 mg / mL.
8. The preparation method according to claim 6, characterized in that: Step 6) In the sodium hyaluronate composite filler: The concentration of the methoxy polyethylene glycol-poly-L-lactic acid nanoparticles is 5 mg / mL to 300 mg / mL; The molecular weight of sodium hyaluronate is 2×10 5 ~2.5×10 6 Dalton, the sodium hyaluronate concentration is 5 mg / mL to 30 mg / mL; The average particle size of the methoxy polyethylene glycol-poly (L-lactic acid) nanoparticles is 10 nm to 500 nm.
9. The preparation method according to claim 6, characterized in that: The organic solvent is selected from at least one of ethanol, methanol, acetonitrile, chloroform or dichloromethane.
10. Use of the sodium hyaluronate composite filler according to any one of claims 1 to 5 or the sodium hyaluronate composite filler prepared by the preparation method according to any one of claims 6 to 9 in tissue repair materials and / or filling biomaterials.
Citation Information
Patent Citations
Skin filler used for injection and preparing method and application thereof
CN105749359A
Injection filler and preparation method thereof
CN116370707A
Injection type plastic and aesthetic filler composition as well as preparation method and application thereof
CN116370716A
Preparation method of injectable sodium hyaluronate coated polylactic acid microspheres
CN116421779A
Hydrophilic injection-type skin filling composition, and preparation method and application thereof
JP2023064714A